Measuring internship quality in education: A Systematic review and comparative synthesis of internship scales - Olievia Prabandini Mulyana; Nur Hidayah; Nur Eva; Ninik Setiyowati; Amin Al Haadie Shafie (Jurnal Pendidikan Vokasi, 2025)
Internship programs play a strategic role in bridging academic learning and workplace practice; however, the quality of these programs is often assessed using diverse and fragmented instruments. The absence of standardized and theoretically robust internship quality scales has resulted in inconsistent measurement, limiting cross-study comparability and evidence-based improvements. This study systematically reviews and compares measurement scales that have been used to evaluate the quality of internship programs in educational contexts. Employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, articles were identified from Scopus and Google Scholar using predefined keywords, screened through identification, eligibility, and inclusion stages, and filtered based on year of publication (2000–2024), focus on internship quality, explicit reference to measurement instruments, and student samples. Twelve empirical studies met the inclusion criteria. The review highlights several key instruments, including the Job Diagnostic Survey (JDS), Internship Quality Inventory (IQI), Questionnaire for Professional Training Evaluation (Q4TE), Vocational Internship Evaluation Scale, and other adapted scales. Findings show that while employee-based instruments (e.g., JDS) capture job characteristics and motivation, education-specific scales (particularly IQI) provide a more comprehensive conceptualization by integrating autonomy, supervision quality, learning opportunities, and social support. Nonetheless, none of the identified scales fully address contextual, cultural, and programmatic variations across institutions. This review contributes a consolidated mapping of internship quality scales, clarifies their strengths and limitations, and underscores the need for developing theoretically grounded, context-sensitive, and standardized instruments for educational settings. Future research should emphasize scale validation across cultures and disciplines and integrate mixed-methods approaches to strengthen construct validity and practical relevance.